Hepatic mRNA expression and plasma levels of insulin-like growth factor-I (IGF-I) in broiler chickens selected for different growth rates - Giachetto, Poliana Fernanda [UNESP]; Riedel, Eduardo Correa [UNESP]; Gabriel, Jane Eyre [UNESP]; Ferro, Maria Inês Tiraboschi [UNESP]; Di Mauro, Sônia Marli Zingaretti [UNESP]; Macari, Marcos [UNESP]; Ferro, Jesus Aparecido [UNESP] (Sociedade Brasileira de Genética, 2004)
The hepatic expression and plasma concentrations of IGF-I were investigated in three broiler chicken strains selected for different growth rates (HP-Hubbard-Pettersen, a fast growing strain; NN-Naked-neck, a strain with an intermediate growth rate and a heterozygous genotype, and C-Caipira, a slow growing crossbred strain). The chickens were studied at 1, 21 and 42 days of age and had free access to food throughout the study. Hepatic IGF-I mRNA expression was assessed by dot blot analysis using a randomly labeled chicken IGF-I cDNA as the probe and plasma IGF-I concentrations were assayed by radioimmunoassay. The hepatic levels of IGF-I mRNA increased from 1 to 21 days of age in all strains, with NN chickens showing a higher (p < 0.05) IGF-I expression than the other strains. Plasma IGF-I concentrations increased (p < 0.05) with broiler chicken age, but there were no significant differences among the strains. These results indicate that despite differences in the growth rates among the strains, the changes in the expression of IGF-I mRNA in liver and in the plasma levels of IGF-I were independent of broiler chicken strain, but varied with chicken age.
Keywords: IGF-I mRNA; Broiler chicken; Growth performance; plasma IGF-I